Modelling of the Dynamics of a Hydraulic Positional Cylinder - Dindorf, R. (Engineering Transactions, 1996)
The present paper describes modelling of dynamics, results of simulation and experimental investigation of a hydraulic positional cylinder. The method of bond graph is used for modelling of the dynamics of the considered cylinder design. First, an initial digital simulation is performed in order to calculate basic dynamic characteristics of the cylinder. Next, an additional damping system is applied which affects dynamic characteristics of the considered cylinder. Finally, results of the model simulation are verified experimentally.